RELIABILITY AND VALIDITY OF CARE FOR OLDER ADULTS IN HOSPITALS AND NURSING FACILITIES IN CHINA. (16th November 2018) - Jiang, L; Jiang, C; Cui, Y; Chang, P
Abstract: CARE (Continuity Assessment Record and Evaluation) is a comprehensive geriatric assessment tool. This study aimed to examine reliability and validity of a Chinese version of CARE for older adults in hospitals and nursing facilities in mainland China. The Chinese version of CARE was administered in two samples. Sample 1 included 90 older adults (60 years or older) from hospitals and 60 older adults from nursing facilities to test inter-rater reliability and internal consistency. Sample 2 included 120 older adults from hospitals and 120 older adults from nursing facilities to test criterion-related validity with the Minimum Mental State Examination (MMSE), Barthel index, and Lawton Instrumental Activities of Daily Living (IADL)scale. The paper calculated inter-rater reliability, internal consistency of the subscale and criterion-related validity through intraclass correlation coefficient (ICC), Cronbach alpha coefficient and Spearman correlation coefficient respectively. For hospitals, the ICC ranged from 0.611 and 1.0 at item level and from 0.226 to 1.0 at sub-scale level, excluding one item (ICC = −0.011). For nursing facilities, the ICC ranged from 0.571 to 1.0 at item level and from 0.305 to 0.963 at sub-scale level. Besides, Cronbach alpha coefficients of most sub-scales were higher than 0.7 in both cases. Correlations between CARE sub-scales and instruments for criterion-related validity were excellent (r > 0.8) in both cases too. These results indicated that the Chinese version of CARE was reliable and showed good criterion validity in both hospitals and nursing facilities.